Direito e ciência para Humberto Maturana e Chaïm Perelman - Nadai, André Moraes de (2019)
The object of our dissertation is about knowing the law. Is it through science? Or in another way? To answer these questions, we are based on the Philosophy of Biology of Knowing, by Chilean Professor Humberto Maturana Romesín. Throughout our journey we were attentive to this questioning, which made us look for answers in authors like Chaïm Perelman. From the Maturana’s Gnosiology and Epistemology and based on the theory of the argument of Perelman we were able to find the clarifications that we looked for. It is, therefore, that we present our following work